Written Conversation Technique and its Necessity in Improving Speaking and Writing Proficiencies for EFL Students - Badie, Muthana (Journal of Tikrit university for humanities - مجلة جامعة تكريت للعلوم الانسانية, 2021)
This study aims to investigate the effect of using new strategy (written conversation) in teaching speaking and writing English as a foreign language. Speaking and Writing are the most commonly used and effective means of self- expression in all fields of human life, whether personal, social or professional.  This study is not only an empirical examination of speaking and writing methods but also an attempt to understand the concept of speaking and writing as essential proficiencies in learning English. By reviewing the definitions of speaking and writing and their teaching methods, the study presents the writing and speaking proficiencies in a new frame theoretically and practically. The written conversation technique is intended to improve the students' proficiencies in Writing and speaking through practicing them with their teachers and peers. A test is designed to determine the students' level in speaking and writing and identify the impact of using the new technique (written conversation) on learning the writing and speaking. The experimental design of the study consists of two groups, namely, control group and experimental group, with 40 female students for each. After analyzing the data, the experimental group shows better performance than that of the control one. This indicates that teaching the writing and speaking proficiencies by using written conversation technique is more effective than teaching by traditional method.